Le tarif d’achat photovoltaïque comme outil d’innovation territoriale : l’exemple des Fermes de Figeac - Béatrice Cointe (VertigO)
From 2008 to 2012, the rural cooperative “Fermes de Figeac”, situated in the Southwest of France, carried out a mutualised photovoltaic project that consisted in the installation of photovoltaic systems on about a hundred rooftops. The aim of this project was not only to seize the opportunity provided by feed-in tariffs when they were at their highest level, but also to do so in a mutualized, territorial way. In order to analyse the constitution of an entrepreneurial and financial capacity that is both adapted to the frame of feed-in tariffs and able to transform it, this article looks at the articulation of financial investment, mutualisation and territory as it is performed in the project business model and in its realization.